Application of dissolvable Mg/Al layered double hydroxides as an adsorbent for the dispersive solid phase extraction of gold nanoparticles prior to their determination by atomic absorption spectrometry. Issue 3 (19th December 2019) - Choleva, Tatiana G.; Giokas, Dimosthenis L.
Abstract : In this work, dissolvable layered double hydroxides (LDHs) were used for the first time for the extraction and preconcentration of metallic nanoparticles from water samples. Abstract : In this work, dissolvable layered double hydroxides (LDH) were used for the first time for the extraction and preconcentration of metallic nanoparticles from water samples. Magnesium–aluminum LDHs were prepared in situ in a sample solution by alkaline co-precipitation and separated by centrifugation. It was found that gold nanoparticles (AuNPs) and gold ions could be simultaneously extracted by the LDH by electrostatic interactions and anion exchange reactions, respectively. Separation of AuNPs from gold ions could be achieved by ultracentrifugation enabling the selective determination of AuNPs in the sample. Two analytical techniques based on molecular and atomic spectrometry (spectrophotometry and electrothermal atomic absorption spectrometry) were used to optimize the method and determine the concentration of AuNPs in spiked environmental water samples at femtomolar concentration levels, respectively. Under the optimized experimental conditions the method enables the determination and speciation of AuNPs at concentration levels as low as 16 femtomole L −1 with satisfactory recoveries (71–91%) and good reproducibility (<9%).